Behavioral Problems in Domestic Cats of Tehran: N. Tamimi*; A. Talebi; A. Malmasi; F. Tamimi and A.Amini - Tamimi, N. (The Iraqi Journal of Veterinary Medicine, 2012)
Behavioral problems are very important because they are one of the most common reasons for the relinquishment of cats. In this study, the frequency of behavioral problems in 167 cats attending Small Animal Hospital, Faculty of Veterinary Medicine, University of Tehran, was evaluated with the use of a questionnaire. Interaction with other animals and people, outdoor access, breed, and sex of the cats were evaluated for association with the occurrence of the behavioral problems. Aggression towards people and other cats, Elimination problems, Scratching objects, Fearfulness, Attention seeking, Excessive grooming, Chasing small animals, Hiding, Vocalization in owner’s absence, Obsessive behaviors and Eating fiber material were the behavioral problems evaluated in this study. Results showed that 94.6% of the cats were reported to have at least one behavioral problem with the mean number of behavioral problems for one cat being 2.71. Fearfulness, attention seeking, Aggression towards other cats/people, scratching, and Elimination problems were the most prevalent behavioral complaints reported by cats owners respectively whereas; obsessive behaviors were the least common behavioral complaints.Data analysis revealed that inappropriate elimination is significantly more common in cats with outdoor access while interaction with other cats and people showed an association with scratching in cats. Intact female cats tended to seek less attention from their owners than their other counterparts. Breed assessment, on the other hand, showed that Persian cats are reported to have more elimination problems and less aggression problems towards people than DSH cats.